HIV continuum of care: bridging cross-sectional and longitudinal analyses. (15th March 2022) - Touloumi, Giota; Thomadakis, Christos; Pantazis, Nikos; Papastamopoulos, Vasileios; Paparizos, Vasilios; Metallidis, Simeon; Adamis, Georgios; Chini, Maria; Psichogiou, Mina; Chrysos, Georgios; Sambatakou, Helen; Barbunakis, Emmanouil; et al.
Abstract : Objective: The aim of this study was to propose a unified continuum-of-care (CoC) analysis combining cross-sectional and longitudinal elements, incorporating time spent between stages. Design: The established 90-90-90 target follows a cross-sectional four-stage CoC analysis, lacking information on timing of diagnosis, antiretroviral therapy (ART) initiation, and viral suppression durability. Methods: Data were derived from the Athens Multicenter AIDS Cohort Study (AMACS). In the cross-sectional CoC, we added stratification of diagnosed people with HIV (PWH) by estimated time from infection to diagnosis; of those who ever initiated ART or achieved viral suppression by corresponding current status (in 2018); and cumulative incidence function (CIF) of ART initiation and viral suppression, treating loss-to-follow-up (LTFU) as competing event. Viral suppression was defined as viral load less than 500 copies/ml. Viral suppression durability was assessed by the CIF of viral load rebound. Findings: About 89.1% of PWH in 2018 were diagnosed (range of diagnoses: 1980–2018). Median time to diagnosis was 3.5 years (IQR: 1.1–7.0). Among diagnosed, 89.1% were ever treated, of whom 86.7% remained on ART. CIF of ART initiation and LTFU before ART initiation were 80.9 and 6.0% at 5 years since diagnosis, respectively. Among treated, 89.4% achieved viral suppression, of whom 87.4% were currently virally suppressed. The CIF of viral load rebound was 24.2% at 5 years since first viral suppression but substantially reduced in more recent years. Interpretation: The proposed analysis highlights time gaps in CoC not evident by the standard cross-sectional approach. Our analysis highlights the need for early diagnosis and identifies late presenters as a key population for interventions that could decrease gaps in the CoC.